Food policy and security issues : the need for increase investments - Mohayidin, Mohd. Ghazali; Chiew, Eddie F. C.; Mohd. Nor, Zaleha (1986)
The authors, in the first section of this paper, review the world food situation, productivity growth and its determinants. Various features of international agricultural trade policies, the new protectionism and current trade liberalization talks are highlighted. A discussion of some issues of agriculture policies, both macroeconomic and sectoral policies follows. Elements of the National Agricultural policy are then analysed with regards its direction and rationale. The second section examines the National Agricultural Policy in more detail followed by an overview of investment opportunities in Malaysia.